Analisis Strategi Pemasaran Produk Skintific Di Kalangan Milenial - Deshinta Maia; Aini Pungki Sri Rahayu; Syamsul Hidayat (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
This research aims to find out what the marketing strategy is for skintific products, especially among millennials. The method in this research uses qualitative methods while the population in this research is Bina Bangsa University students in the 5th semester majoring in management. The sampling technique used was random sampling by distributing questionnaires online. There were 88 students who filled out the questionnaire so that the sample determined was 88 samples. The results of the research show that the marketing strategy carried out by skintific products with cognitive, affective and conative dimensions with the sub dimensions of product quality, brand, price, promotion and purchasing decisions all have good categories, so the conclusion regarding the strategy carried out by skintific products, especially among millennials, is Good.